2010
DOI: 10.1103/physrevc.82.044617
|View full text |Cite
|
Sign up to set email alerts
|

Reactions with the double-Borromean nucleusHe8

Abstract: Differential cross-sections for elastic scattering and neutron transfer reactions along with crosssections for fusion in the 8 He+ 65 Cu system are reported at energies above the Coulomb barrier (E lab = 19.9 and 30.6 MeV). The present work demonstrates the feasibility of using inclusive measurements of characteristic in-beam γ rays with low-intensity (∼ 10 5 pps) radioactive ion beams to obtain the residue cross-sections for fusion and neutron transfer. Exclusive measurements of γ rays in coincidence with lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…[40]. 120 Sn [46], 206 Pb [47] and 208 Pb [48][49][50]; (iii) 8 He on 65 Cu [51]. We discuss below some results showing the damping of the rainbow maximum for these systems.…”
Section: Basic Theory and Recent Measurementsmentioning
confidence: 95%
See 2 more Smart Citations
“…[40]. 120 Sn [46], 206 Pb [47] and 208 Pb [48][49][50]; (iii) 8 He on 65 Cu [51]. We discuss below some results showing the damping of the rainbow maximum for these systems.…”
Section: Basic Theory and Recent Measurementsmentioning
confidence: 95%
“…Thus, it has been accomplished in very few situations. The main examples are the experiments on collisions of 6 He projectiles on 209 Bi, performed in Notre Dame [129,[146][147][148], and collisions of the same projectile on 65 Cu and on 197 Au targets [51,149] and on 9 Be [150].…”
Section: The Reaction Cross Section Extracted From Elastic Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have shown that dynamic effects such as low-lying vibrational couplings [3][4][5] and transfer reactions [6][7][8][9][10] strongly affect fusion reactions. Other dynamic effects, such as breakup [11][12][13][14] and rotational couplings [4], have also been seen to play a role.…”
Section: Introductionmentioning
confidence: 99%
“…8 He is the lightest skin nucleus and it has the largest neutron-to-proton ratio of the particle-stable nucleus. Only a few scattering data sets at barrier energies are presently available [1,2] and there is still a lack of information concerning collective aspects as characteristic nuclear excitations, coupling between different reaction channels and neutron-core correlations.…”
Section: Introductionmentioning
confidence: 99%